2007
DOI: 10.1590/s0100-736x2007000400005
|View full text |Cite
|
Sign up to set email alerts
|

Pré-compostagem de cadáveres de bovinos acometidos pelo botulismo

Abstract: Five carcasses of cattle that died from botulism were composted in individual isolated beds with the purpose of monitoring the effect on spores of Clostridium botulinum and of botulinum toxin. The diagnosis of botulinum poisoning was based on clinical and pathological, epidemic and/or laboratorial characteristics. Of the five bovines with clinical signs of chronic botulism, three were affected by the type D toxin, one by the CD complex, and one was negative for toxin and spores of C. botulinum in the viscera u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 7 publications
1
6
0
4
Order By: Relevance
“…In the case of pigs that die during the breeding process, an opportunity to increase the energy converted (output) in the form of compost (manure), is through the realization of composting carcasses of these animals (CURCI et al, 2007;SANTOS & LUCAS JUNIOR, 2004). Furthermore, composting of dead animals contributes to the inactivation of pathogenic bacteria, viruses and parasites (CURCI et al, 2007;ORRICO JUNIOR et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of pigs that die during the breeding process, an opportunity to increase the energy converted (output) in the form of compost (manure), is through the realization of composting carcasses of these animals (CURCI et al, 2007;SANTOS & LUCAS JUNIOR, 2004). Furthermore, composting of dead animals contributes to the inactivation of pathogenic bacteria, viruses and parasites (CURCI et al, 2007;ORRICO JUNIOR et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, composting of dead animals contributes to the inactivation of pathogenic bacteria, viruses and parasites (CURCI et al, 2007;ORRICO JUNIOR et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Those authors observed 100% reduction, with numbers of 1.1 x 10 8 NMP g -1 in the beginning and 0 NMP g -1 at the end of composting for total and thermotolerant coliforms. Other studies, such as those of Curci et al (2007), Torres et al (2007), and Orrico et al (2007), also observed that composting was efficient to eliminate pathogenic microorganisms. The maintenance of bacterial counts in the present study may have been due to shorter fermentation time, favoring further nitrogen reduction.…”
Section: Resultsmentioning
confidence: 79%
“…Os RSSA de origem orgânica como carcaças e placentas podem ser tratados pelo sistema de compostagem, atingindo os objetivos sanitários, ambientais e econômicos desse procedimento; portanto, esse sistema atende plenamente ao que deve estar previsto em um PGRSS (CURCI et al, 2007;CESTONARO et al, 2010;SOTO et al, 2010;VALENTE;XAVIER, 2015). Esse sistema vem obtendo resultados satisfatórios, tornando-se uma importante forma de tratar os resíduos orgânicos (SUNADA et al, 2014).…”
Section: Tratamento E Disposição Final Dos Rssaunclassified